Analysis of the relationship between antineoplastic drugs and suicide-related adverse events based on the food and drug administration adverse event reporting system database - Nan Zhao; Huimin Wang; Huilin Xu; Xixian Tang; Dedong Cao (SAGE Open Medicine)
Background: The potential association between new antineoplastic drugs and an increased risk of suicide-related adverse drug reactions remains unclear. This study aims to utilize the FAERS public database to analyze suicide-related adverse drug reactions associated with common antitumor drugs and to investigate potential risk signals for such adverse drug reactions. Methods: This study was a retrospective analysis utilizing the FAERS database. The FAERS database was examined for reports of suicide-related adverse events associated with antitumor drugs, spanning from 2004 to 2023. To identify and verify adverse event signals, we employed reporting odds ratios, proportional reporting ratios, and Bayesian methods (Bayesian Confidence Propagation Neural Network). Additionally, logistic regression analysis was performed to assess outcomes in tumor patients. Results: A total of 223,781 suicide-related adverse event reports were screened, of which 3790 involved common antitumor drugs. The top five drugs reported were tretinoin ( n  = 1220), methotrexate ( n  = 664), celecoxib ( n  = 505), rituximab ( n  = 107), and imatinib ( n  = 105). Risk signal analysis indicated that, with the exception of tretinoin (ROR = 6.317), the reporting odds ratio values for the other drugs were below 2. Among cancer patients, the most frequently reported adverse events included suicidal ideation ( n  = 233), completed suicide ( n  = 131), and suicide attempts ( n  = 97). Regression analysis revealed that risk factors for patient death included indication (OR = 0.967, p  < 0.01), gender (OR = 0.57, p  < 0.01), and type of adverse event (OR = 4.644, p  < 0.01). Conclusion: The findings suggest that antineoplastic drugs may not statistically increase the risk of suicide-related adverse events. However, specific tumor types and suicide-related adverse events may contribute to increased mortality in cancer patients. Further research is warranted to elucidate the risk of suicide-related adverse events in oncology patients.